Clinical and epidemiological characterization of patients with nasal fracture treated in a Cuban university hospital - Ibraín Enrique Corrales-Reyes; Alejandro Ernesto Núñez-Blanco; Denia Morales-Navarro (Editorial Ciencias Médicas, 2023)
Introduction: Nasal fractures are the most common fractures of the maxillofacial region. However, Cuban literature on the subject is scarce and outdated, so the motivation for this research arose. Objective: To characterize patients with nasal fractures treated in a Cuban university hospital in a clinical and epidemiological manner. Methods: An observational, descriptive and cross-sectional study was carried out in patients treated at the Maxillofacial Surgery Service of the University General Hospital. "Carlos Manuel de Céspedes" of Bayamo, Granma province, Cuba, from January 1 to December 31, 2020. Clinical, epidemiological and therapeutic variables were studied. Results: 99 patients were included, of whom 74 (74.75 %) were male. In 44.44 % of the cases the ages were between 21 and 40 years. Fifty patients (50.51 %) had fractures resulting from interpersonal violence. Ninety-seven patients (97.98 %) presented epistaxis. Fifty-nine patients (59.60 %) received closed reduction associated with nasal packing and external fixation with plaster cast. Conclusions: Male gender and age group 21 to 40 years predominated. The main etiology was interpersonal violence. Epistaxis was present in most cases. Closed fractures prevailed, as well as those with laterally deviated dorsum.